AB0514 The effect of hydroxychloroquine on reducing proteinuria in stable sle patients. (12th June 2018) - Takahashi, H.; Nasa, Y.; Takamasu, E.; Sugii, S.; Yokogawa, N.
Abstract : Background: It is thought that hydroxychloroquine (HCQ) reduces proteinuria by preventing endothelial dysfunction in mouse models, but the effects in systemic lupus erythematosus (SLE) patients are not known. Objectives: To investigate the effects of HCQ on proteinuria in stable SLE patients. Methods: This was a single-centre, retrospective cohort study. We included stable SLE patients who met the updated or revised American College of Rheumatology 1997 criteria for SLE or the 2012 Systemic Lupus International Collaborating Clinics criteria, and had no active organ dysfunction that needed an increase in immunosuppressive therapy. The subjects (HCQ group) were SLE patients with proteinuria >0.2 g/gCr who started HCQ between 11/1/2015 and 8/1/2017. The controls (non-HCQ group) were SLE patients with proteinuria >0.2 g/ gCr seen between 5/1/2016 and 10/31/2016. The reduction in proteinuria over 6 months in the HCQ and non-HCQ groups was compared. The following patients were excluded from the analysis: those who had proteinuria of other aetiologies (diabetic nephropathy, etc.), those who increased the prednisolone (PSL) dose or started immunosuppressive agents, angiotensin converting enzyme inhibitors, or angiotensin II receptor blockers beginning 1 month before the observation period started until its end. Improvement was defined as a reduction in proteinuria ≥0.1 g/gCr. The statistical analysis was performed with the t- test and chi-square test. Results: There were no significant differences in disease duration, sex, Systemic Lupus Erythematosus Disease Activity Index, or the use of immunosuppressants at baseline between the HCQ (n=16) and non-HCQ (n=14) groups. The respective mean PSL dose at baseline was 5.9±2.8 and 3.3±3.8 mg in the HCQ and non-HCQ groups (p=0.042). Patients in the HCQ group were younger (mean 47±12 vs . 63±14 years, p=0.005). The kidney pathology of the HCQ group was 6.25, 25, 6.25, 6.25, and 6.25% class I to V, respectively, compared with 7.14% class IV, 14.2% class V, and 14.2% class IV+V in the non-HCQ group. The other patients were diagnosed with lupus nephritis clinically. Proteinuria was significantly lower in the HCQ group than in the non-HCQ group (–0.170±0.343 g/gCr vs . +0.129 ±0.401 g/gCr, p=0.036). The mean proteinuria at baseline and 6 months later was 0.501±0.276 and 0.331±0.274 g/gCr, respectively, in the HCQ group, and 0.587±0.409 and 0.717±0.720 g/gCr in the non-HCQ group. The proportion of patients who improved in the HCQ and non-HCQ groups was 68.7% (11/16) and 28.5% (4/14), respectively (p=0.028). Conclusions: HCQ may reduce proteinuria in SLE patients. This suggests that HCQ administration protects the kidneys of SLE patients. Disclosure of Interest: None declared